أثر تطبيق معايير التدقيق الجزائرية على تحسين جودة القوائم المالية - دراسة ميدانية للمعيار 530 السبر في التدقيق - سناء بن جاب الله; ابتسام ماضي (My University, 2022)
This study aimed to identify the extent to which the application of the Algerian Standard for Auditing 530 “Sounding in Auditing” is related to the quality of the financial statements. In order to reach study's goal, a questionnaire was used, distributed to professionals and academics in Souk Ahras state, where SPSS version 22 was used for data analysis. The study concluded that there is a strong correlation between the Algerian auditing standard 530 “sounding in the audit” and financial statements quality, as the sounding in the audit application leads to raising financial statements level quality and giving them more credibility, transparency and acceptance by the parties that use them, with the least time and cost. .......................................................